The Clove Business Development Strategy in Lambandia District East Kolaka Regency - Fitri Andriani; Ine Fausayana; Munirwan Zani (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2022)
This research aims to assess the clove growing revenue and development plan in Lambandia District, East Kolaka Regency. This research was conducted in Mokupa Village and Penanggootu Village, Lambandia District, East Kolaka Regency, from 18 to 25 August 2021. The population in this study was 81 people. The sample was taken using simple random sampling of as many as 45 people. The analytical method used is descriptive, income, SWOT. The results showed that the average income of clove farmers from the income, the average production cost is reduced by IDR26.307.864/farmer. The clove farming development strategy is at the coordinates point of quadrant 1, namely the aggressive strategy or SO strategy. This shows that the state of the clove farming development strategy shows a very favorable situation for the development of clove farming in Lambandia District, East Kolaka Regency, which has strengths and opportunities that are unified and mutually supportive, using strength factors to take advantage of existing opportunities. So that a strategy can be produced that can be carried out in the development of clove farming, namely the SO strategy consisted of improving product quality, increasing production, expanding the planting area. ST strategy consists of minimizing expenses, increasing skills and insight into the technology used in farming. The WO strategy consists of creating a community or joining an existing community to increase information, insight, and knowledge in farming, setting aside income to be used as capital for developing clove farming. The WT strategy consists of adding other short-term farms.